Autologous Mesenchymal Stem Cell Transplantation for the Treatment of Chronic Heart Failure in Dilated Cardiomyopathy: A Clinical Case - Yulia V. Ivanova; Svetlana M. Gramatiuk; Sergii I. Estrin; Igor A. Kryvoruchko; Tetiana V. Kravchenko; Yakiv O. Peremot; Andrii O. Kovalchuk (Український журнал серцево-судинної хірургії)
Dilated cardiomyopathy (DCMP) occupies a significant place among non-coronary heart diseases leading to chronic heart failure (CHF). Due to the high mortality rate associated with DCMP, there is a continuous search for alternative heart-preserving treatment methods as “bridges” to heart transplantation. One of the promising approaches is stem cell therapy.